Restriction of the growth of T7-like phages by plasmid prophage P1 - Faidiuk, I.V. (Фактори експериментальної еволюції організмів, 2014)
Aims. Considerable part of T7 phage genome is responsible for interaction with the bacterial host, primarily for the avoidance of action of protective systems of cells, the restriction-modification complexes. Interactions of T7-like phages with RM systems of type I and II are relatively studied while the question of impact by the type III systems on their growth remains unclear. Developing a relevant system would allow us to study the interaction of bacteriophages with host cells on the gene level including the interplay with prophage elements and RM-systems. Methods. Biological, genetics and molecular biology approaches combined with bioinformatic research were used. Results. The ability of P1 to infect and lysogenise Erwinia amylovora and Erwinia “horticola” cells as well as its maintainance as a single-copy plasmid in the cells of uncommon hosts was shown. A set of lysogenic strains was obtained. According to the level of restriction three types of phage-RM system interaction were discovered. Though polyvalent, phage FE44 undergoes abortive infection similar to other members of T7 phage group. Conclusions. The genes of restriction-modification complex EcoP1I are fully expressed regardless the bacterial host lysogeinzed by phage P1. Differences in interaction with cells are likely associated with the number of enzyme recognition sequences and the adsorption sites availability while gp 0.3 Ocr protein is not involved in this interaction. The constructed systems allow for the exploration of EcoР1I interaction with polyvalent phages able to grow both on E. coli and on such phytopathogens as E. “horticola” and E. amylovora.